AGE-RELATED FEATURES OF THE MANIFESTATION OF THE LEVEL OF ANXIETY IN DIVERS IN THE ASSESSMENT OF NEGATIVE MENTAL STATES - Milashechkina, E.A.; Milashechkina, V.V.; Potapov, D.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify age-related features of the manifestation of anxiety, aggressiveness, hostility in high-sport divers. Methods and structure of the study. The scientific work involved 37 adolescents aged 11-15 years old engaged in diving at the Aquatika sports school in the city of Kazan (experimental group) and 59 adolescents not involved in sports (control group). Results and conclusions. In the course of the study, water jumpers showed a high level of anxiety on all scales compared with the results of adolescents in the control group. The level of aggressiveness and hostility in adolescents of the experimental group throughout the entire period of ontogenesis under study is within the normal range, and in boys of the control group, hostility at the age of 12-14 is significantly higher than in adolescents of the experimental group. High levels of anxiety in water jumpers do not affect the manifestation of negative mental states of the individual.